THE The Influence Of Career Development, Work Motivation And Individual Characteristics On Employee Job Satisfaction At The Djp North Sumatra I Regional Office - Gunawan Ritonga, Dedy; Kariaman, Kariaman; Kadafi, Muhammad; Ulfa, Maria; Safrida, Safrida; Wasesa, Supar (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The purpose of this study is to ascertain whether employee job satisfaction at the DJP North Sumatra I Regional Office is influenced by career development, work motivation, and individual characteristics simultaneously or in part. The examination was led at the North Sumatra I DJP Provincial Office Jalan Sukamulia No. 17A Medan, with a population of 145 individuals and an exploration test of 59 individuals. Information assortment was completed through meetings, polls and documentation. Using version 24 of the IMB Statistics for Product and Service Solution (SPSS) computer program, multiple regression analysis was used to analyze the data. In view of the consequences of the examination, it was found that profession improvement meaningfully affects work fulfillment for representatives of the North Sumatra Provincial Office of DJP I. This is upheld by the investigation results t count > t-table (2.077 > 2.004) at n = 59 at an importance level of 95%. Work inspiration meaningfully affects the work fulfillment of representatives of the DJP North Sumatra Local Office I; this is upheld by the examination of t count > t-table (5.857 > 2.004) at n = 59 at an importance level of 95%. Individual qualities affect the work fulfillment of representatives at the North Sumatra Local Directorate General Office I; this is upheld by the t count < t-table examination (1.326 < 2.004) at n = 59 with an importance level of 95%. The F-count esteem > F table (50.623 > 2.78) expresses that together (differently), there is a positive and huge effect on profession improvement, work inspiration and individual qualities on the work fulfillment of representatives of the North Sumatra Local Office of DJP.